Prehod na COBISS v knjižnici OŠ Vodice - Ščavničar, Urška (Šolska knjižnica, 2016)
In December 2015, the Act Amending the Librarianship Act entered into force; it requires school libraries to join the COBISS system within the next three years. The paper presents the experience of the library of the Vodice Primary School with switching to the COBISS system before the act entered into force. It presents the reasons for deciding to switch to it, the process of switching to it, and coordinating it with the librarian's other work. The author highlights the opportunities offered by switching to COBISS and points out the important stages in the process of switching to it.
Keywords: COBISS; knjižnične zbirke; konverzija; šolske knjižnice; vzajemna katalogizacija; Zakon o knjižničarstvu